Identify self – fitness profiling among urban Malaysian individuals age 50’s / Chee Hian Tan … [et al.] - Tan, Chee Hian; Jung, Young Lee; Md Yusuf., Mohd Khairulanwar; Raja Azidin, Raja Mohammed Firhad (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2019)
This study aimed to identify self- fitness profiling and describe effectiveness of “APecR” on Malaysian individuals aged 50’s in the complications modern life concerned. Twenty (n = 20) participants [(age = 52 ± 3 years)., (weight = 83 ± 1.5kg)., & (height = 168 ± 30cm)] voluntarily recruited. Workload, heart rate, sleeping pattern, blood pressure and energy intake and expenditure were recorded for 3 continuous cycles (3 months). Findings revealed 42.2% participants were very active (> 12,000 steps), 9.7% was active (> 10,000 steps), 0.11% was moderately active (7,500- 9,999 steps), 22.6% was not active (5000 – 7499 steps) and 16.2% was sedentary (< 5,000 steps). Participants’ average running steps, active time, total distance covered and energy expenditures during the first, second and third month were [(11,161 steps, 2 hours 5 min, 247.1 km distance and 1394 kcal)., (13,197 steps, active time 2 hours 19 min, , 296.8 km distance covered and 10,090 kcal)., and average of 11, 005 steps, active time 2 hours 5 mins, distance covered of 235.5 km and energy expenditures of 8528 kcal)] respectively. 30% of the participants blood pressure were normal (120/80 mm Hg), 43% was pre - high blood pressure (130-140/80-90 mm Hg) and 27% participants were in the high blood pressure category. Findings also revealed the participants gained longer sleeping time (7 hours 7 mins) at post “APecR” compared to pre – “APecR” (6 hours 46 mins). All participants demonstrated an average of moderate level of intensity. These finding suggested by identifying fitness status and delivering individuals’ fitness profile were vital important role in promoting active lifestyles in elderly age 50’s population.